If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -22 = 110 Reorder the terms: -22 + 12x = 110 Solving -22 + 12x = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 12x = 110 + 22 Combine like terms: -22 + 22 = 0 0 + 12x = 110 + 22 12x = 110 + 22 Combine like terms: 110 + 22 = 132 12x = 132 Divide each side by '12'. x = 11 Simplifying x = 11
| -5(b-1)=30 | | -5x(b-1)=30 | | x^4-34x=-225 | | 2m(n-8)-(n-8)=0 | | 5x(3x^2+7)-4(3x^2+7)=0 | | -16x^2+4.51x+32.81=0 | | log[5](64)-log[5]+log[5](2)=log[5](4p) | | Z^2+9z-2=0 | | r^2-5r+7=0 | | -3(f-9)=4f-9f | | WHATDOESB= | | 3x-75x+105=-3 | | 100x^2=36 | | -5g-4+3g=(4-3g)2 | | 0=7u-4-2+5u | | 3A-13=7+A | | n-4=19 | | n+36=54 | | -17+10= | | 45X+6X-78=463 | | 39X+22=124 | | -6z+5=17 | | -5t-5=12 | | x=5*7+9 | | -6s+5=-22 | | 10+(-8)= | | -2r+4=7 | | x+18-5x=18 | | -15-4r=1 | | 10-7a=24 | | 13-2m=25 | | (6.3x-1.4)+(3.7x-1.6)=4(2.5x-0.75) |